A Tale of Two Cities and One Exhibition - Linda Pillière (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2025)
This study focuses on the interpretation labels of two city museums, the Cité des Sciences, and the Museum of London, and more specifically on those used in the exhibition “La Ville est à Nous”/ “The City is Ours” which was held in both cities. From the outset, this exhibition was advertized as a dual-language exhibition, with labels for the exhibits in English and in French, both in London and in Paris. However, the press reviews were less than enthusiastic when the exhibition transferred to London. This article seeks to discover the underlying reasons for this response by comparing and contrasting the two museums’ narratives, and the way they communicate with museum visitors through exhibition labels and text but also in terms of the organisation of narrative space.